Physical comorbidities of post‐traumatic stress disorder in Australian Vietnam War veterans. Issue 6 (3rd April 2017) - McLeay, Sarah C; Harvey, Wendy M; Romaniuk, Madeline NM; Crawford, Darrell HG; Colquhoun, David M; Young, Ross McD; Dwyer, Miriam; Gibson, John M; O'Sullivan, Robyn A; Cooksley, Graham; Strakosch, Christopher R; Thomson, Rachel M; et al.
Abstract: Objective: To determine whether the prevalence of physical comorbidities in Australian Vietnam War veterans with post‐traumatic stress disorder (PTSD) is higher than in trauma‐exposed veterans without PTSD. Design, setting and participants: Cross‐sectional analysis of the health status (based on self‐reported and objective clinical assessments) of 298 Australian Vietnam War veterans enrolled by the Gallipoli Medical Research Institute (Brisbane) during February 2014 – July 2015, of whom 108 were confirmed as having had PTSD and 106 served as trauma‐exposed control participants. Main outcomes and measures: Diagnostic psychiatric interview and psychological assessments determined PTSD status, trauma exposure, and comorbid psychological symptoms. Demographic data, and medical and sleep history were collected; comprehensive clinical examination, electrocardiography, spirometry, liver transient elastography, and selected pathology assessments and diagnostic imaging were performed. Outcomes associated with PTSD were identified; regression analysis excluded the effects of potentially confounding demographic and risk factors and comorbid symptoms of depression and anxiety. Results: The mean total number of comorbidities was higher among those with PTSD (17.7; SD, 6.1) than in trauma‐exposed controls (14.1; SD, 5.2; P < 0.001). For 24 of 171 assessed clinical outcomes, morbidity was greater in the PTSD group, including for conditions of the gastrointestinal, hepatic, cardiovascular, and respiratory systems, sleep disorders, and laboratory pathology measures. In regression analyses including demographic factors, PTSD remained positively associated with 17 adverse outcomes; after adjusting for the severity of depressive symptoms, it remained significantly associated with ten. Conclusion: PTSD in Australian Vietnam veterans is associated with comorbidities in several organ systems, independent of trauma exposure. A comprehensive approach to the health care of veterans with PTSD is needed.